HEALTHCARE TECHNOLOGY MANAGEMENT IMPLICATIONS USING ARTIFICIAL INTELLIGENCE FOR HEALTHCARE INDUSTRY - Ezekiel Anthony; Norshahrizan Nordin; Wei Chern Ang, (Journal of Human Development and Communication (JoHDeC), 2025)
This research is designed to investigate the usage of Artificial Intelligence (AI) in Healthcare Technology Management and to present its impacts on Employee Engagement among healthcare workers. The fast growth of data in healthcare has created an ideal environment for the development of Artificial Intelligence (AI). Healthcare workers have experienced a paradigm shift brought on by Artificial Intelligence, which promises to increase the quality of services provided. This research ID of: RSCH ID-22-05617-MT2 under National Medical Research Registration under protocol: Protocol UniMAP TIOHTMUAIFEE.